Cluster analysis of family resilience in adolescents with emotional disorders: a cross-sectional study - Jun Shen; Shuang Zhou; Miao Du; Biyun Xia; Ying Jiang (BMC Psychiatry)
Abstract Objectives This study evaluated the current state of family resilience in adolescents diagnosed with emotional disorders, incorporating perspectives from both the patients and their primary caregivers. Method A cross-sectional study design was employed, involving 281 adolescent aged 12 to 18 years diagnosed with emotional disorders and their primary caregivers, recruited from a psychiatric specialty hospital in China between December 2023 and July 2024. Both groups completed standardized assessments of family resilience and family functioning. K-means cluster analysis was conducted using Python 3.12.4 software, and statistical analyses were conducted with SPSS 25.0. Results Five distinct clusters of family resilience were identified based on scores from both patients and primary caregivers, including Dual Adversity (18.50%), Caregiver-Empowered (10.32%), Balanced and Coordinated (46.26%), Patient-Strength (11.39%), and Divergent-Challenge (13.52%). Significant differences were observed across clusters in family functioning, socioeconomic factors (such as medical payment methods, monthly household income, caregiver employment status), family relationship quality (including parent-child relationship, marital relationship, and parenting style), and disease-related characteristics (such as distress and self-discontinuation of psychiatric medication). Primary caregivers reported higher levels of family resilience and functioning than adolescents. Additionally, family resilience and family functioning showed significant positive correlations in both adolescents (r = 0.668, p < 0.001) and caregivers (r = 0.405, p < 0.001). Conclusions This study, through a dual patient-caregiver perspective and cluster analysis, highlights the diversity and complexity of family resilience in adolescents with emotional disorders. The findings identified five distinct cluster patterns, underscoring the strong association between family resilience and family functioning. Based on the characteristic differences among these clusters, clinical practitioners can formulate tailored family-based intervention strategies aimed at enhancing overall family resilience and optimizing family functioning, thereby improving treatment outcomes and quality of life for adolescents with emotional disorders.